Levels of Hell in the Sunnah - ALWAN, MOHAMMED HAMEED (Journal of Ecohumanism, 2024)
This research is allocated to studying what is stated in Sunnah about the levels of Hell, to derive benefits from it and prove the facts. Its importance comes from the absence of an independent study on this topic. After the introduction, I divided the research, into an introduction and two sections: The first section: The partitions of the levels of Hell, and the second section: The lowest level of Hell. Then I concluded the research with a conclusion in which I showed the most important results, then a list of sources and references. It has been proven that Hell has seven gates and that each gate represents a level of the levels of Hell. As for the names of these levels and who will be punished in them, this has not been proven by any authentic Hadith. It has also been proven that the people of Hell vary in the degrees of their punishment, and that the lowest level of Hell is its bottom, and its depth is enormous, estimated at seventy years for the sake of increasing, where the hypocrites, the oppressors, and the arrogant reside.